2013
DOI: 10.18632/oncotarget.1145
|View full text |Cite
|
Sign up to set email alerts
|

Clonogenic Multiple Myeloma Cells have Shared stemness Signature Associated with Patient Survival

Abstract: Multiple myeloma is the abnormal clonal expansion of post germinal B cells in the bone marrow. It was previously reported that clonogenic myeloma cells are CD138−. Human MM cell lines RPMI8226 and NCI H929 contained 2-5% of CD138− population. In this study, we showed that CD138− cells have increased ALDH1 activity, a hallmark of normal and neoplastic stem cells. CD138−ALDH+ cells were more clonogenic than CD138+ALDH− cells and only CD138− cells differentiated into CD138+ population. In vivo tumor initiation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 46 publications
2
34
1
1
Order By: Relevance
“…It has been shown that: a)-only CD138 − MM cells have the clonogenic potential and are able to propagate MM tumor in NOD/SCID mice, b)-MMCSCs carry the immunophenotype signature CD138 − /CD19 + /CD20 + /CD27 + , indicating that MMCSCs possess a memory B cell-like phanotype signature arising from a hierarchical pre-malignant plasma cell stage, c)-In a novel 3D model drug resistant MM cells were CD20 + [237], and MMCSCs growth was inhibited by rituximab (anti-CD20 mAb), d)-MMCSCs (CD138 − MM cells) are resistant to dexamethasone, lanalidomide, bortezomib, are enriched in a side population (SP) with high ALDH1 activity and drug efflux pump [238], and recently e)-CD138 − MM cells are ALDH + , have a higher clonogenic potential than CD138 + cells and are able to expand tumor in NOG mice [239]. Several previous studies from Pilarski et al also confirmed presence of clonotypic B cells in MM patients contributing to tumor expansion, relapse and DR [240-242].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that: a)-only CD138 − MM cells have the clonogenic potential and are able to propagate MM tumor in NOD/SCID mice, b)-MMCSCs carry the immunophenotype signature CD138 − /CD19 + /CD20 + /CD27 + , indicating that MMCSCs possess a memory B cell-like phanotype signature arising from a hierarchical pre-malignant plasma cell stage, c)-In a novel 3D model drug resistant MM cells were CD20 + [237], and MMCSCs growth was inhibited by rituximab (anti-CD20 mAb), d)-MMCSCs (CD138 − MM cells) are resistant to dexamethasone, lanalidomide, bortezomib, are enriched in a side population (SP) with high ALDH1 activity and drug efflux pump [238], and recently e)-CD138 − MM cells are ALDH + , have a higher clonogenic potential than CD138 + cells and are able to expand tumor in NOG mice [239]. Several previous studies from Pilarski et al also confirmed presence of clonotypic B cells in MM patients contributing to tumor expansion, relapse and DR [240-242].…”
Section: Introductionmentioning
confidence: 99%
“…The use of alternative methods for disease assessment such as imaging techniques (positron emission tomography, computed tomography), 47 monitoring of clonogenic MM progenitors, 48,49 or MM circulating tumor cells, 22,49,50 could provide complementary information to MRD and improve the estimation of the risk of progression.…”
Section: Mrdmentioning
confidence: 99%
“…Matsui et al first described CD138 negative (CD138 − ) population with greater clonogenic potential than CD138 positive (CD138 + ) myeloma cells [15, 16]. CD138 − clonotypic B cells are also found in the peripheral blood and bone marrow of patients with MM [16, 17] and are associated with poor survival of MM patients [18]. Indeed, successful engraftment of CD138 − subpopulation from MM patients, but not CD138 + , in NOD/SCID mice suggested that CD138 − myeloma cells were the principal myeloma initiating cells [19].…”
Section: Introductionmentioning
confidence: 99%